Evaluation of superficially and fully porous particles for HILIC separation of lanthanide–polyaminocarboxylic species and simultaneous coupling to ESIMS and ICPMS. Issue 44 (9th July 2018) - Blanchard, E.; Nonell, A.; Chartier, F.; Rincel, A.; Bresson, C.
Abstract : Application of sustainable chromatographic strategies to reduce effluent volumes generated by HILIC separation of lanthanide–polyaminocarboxylic acid species. Abstract : In this work, amide-bonded columns packed with fully porous particles (FPP) and superficially porous particles (SPP) were evaluated to separate lanthanide–polyaminocarboxylic species by hydrophilic interaction liquid chromatography (HILIC), using two model samples of interest in nuclear and other industrial applications. We assessed the gains achieved by reducing the dimensions of the columns along with the size of the FPPs to sub-2 μm and by using sub-3 μm SPP-packed columns. The FPP-packed Acquity column (100 × 2.1 mm; 1.7 μm) performed better than the SPP-packed Accucore column (150 × 2.1 mm; 2.6 μm), with a separation that was two times more efficient and three times shorter, while generating around 30% less in effluent volumes. This column was also coupled simultaneously to electrospray ionisation mass spectrometry (ESIMS) and inductively coupled plasma mass spectrometry (ICPMS). The instrumental set-up was performed in a conventional laboratory, by taking into account the geometrical constraints existing in the laboratory dedicated to radioelement analysis. Furthermore, separation of the series of lanthanide (Ln) species was demonstrated for the first time thanks to the separation mode of hydrophilic interaction liquid chromatography.